On the Continued Need for Replication in Media and Communication Research - Nicholas David Bowman (Media and Communication, 2024)
Common models of the scientific method articulate the processes by which we hypothesize about the correlation between variables and then test those predictions to make incremental conclusions about the world around us. Implied in this process is the replication and extension of that knowledge to various contexts. As with other social sciences, published analyses have demonstrated that media and communication scholarship suffers from a lack of replication studies, often due to presumptions about the lack of reward or incentive for conducting this work—such as perceived difficulties securing support for and/or publishing these studies. This commentary will reflect on and reinforce arguments for the intentional and important role of replication studies in media and communication scholarship. The essay reflects on replication as a key to post-positivist approaches, and then highlights recent developments that center replication work as key to scientific progression.